Assessment of Impact of Covid-19 Virus on the Obesity and Depression on Patient's at Saudi Arabia in Makkah Al-Mukarramah in 2020 - Safwan Abdulaziz Hamouh, Khalid Abdullah Alrehaili, Rafah Osama Atallah, Bandar Ayidh Alshalawi, Abdulrahman Ghazi Allahyani, Zyaad Fareed Qadi, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The COVID-19 pandemic had a significant impact on daily activities due to restrictions in terms of social distancing because of the elevated rate of contagion and mortality. Many sectors have been affected, worldwide. The world health organization (WHO) declared COVID-19 a worldwide pandemic on 11th March 2020. COVID-19 also referred to as coronavirus disease 2019 is a rising respiratory disease that is caused by a novel coronavirus which was initially detected in December 2019 in Wuhan, China, the disease is extremely infectious and therefore the outbreak has been declared a worldwide pandemic by the WHO. Obesity and overweight are well known risk factors for (COVID-19)disease , and are expected to be increasing in the Kingdom of Saudi Arabia particularly among females. There is a high frequency of increased BMI in patients admitted to intensive care for SARS-CoV-2 infection with a major severity in patients with an excess of visceral adiposity. Patients at risk of severe SARS-CoV-2 acute respiratory syndrome are characterized by the high prevalence of pre-existing diseases (high blood pressure and cardiovascular disease, diabetes, chronic respiratory disease, or cancer), most of them typically present in severely obese patients. Coronavirus illness 2019 (COVID-19) has quickly spread around the world, constraining nations to apply lockdowns and severe social separating measures This study aimed: To assess the impact of COVID-19 virus on the obesity and depression patient's attendants in primary health care center in Makkah Al-Mukarramah. Methods: cross-sectional study was conducted online among Saudi Arabia adults in primary health care center in Makkah Al-Mukarramah. A self-administered questionnaire was designed and has been send to the study participants through social media platforms and email. Our total participants were(300) Results: the majority (43.0%) of the Individuals reported changes in mealtime during the COVID-19 to severe food follow by moderate food were(30.0%), also individuals reporting changes in the daily number of meals consumed during the COVID-19 to moderate food were(31.0%) follow by severe food were (18.0%). Conclusion: results here showed the COVID-19 pandemic is having a significant impact on patients with obesity regardless of infection status. physical inactivity may be a factor that leads to an increase in obesity during Covid-19 Pandemic, the pandemic is having a significant impact on those without infections also .